The Marketing Communication Process of Bakso Terlena in the Implementation of E-commerce in Pancur Batu Deli Serdang - Mitha Suheni; Muhammad Husni Ritonga (UNIVERSITAS PAKUAN, 2023)
The development of internet technology is growing rapidly day by day. With the rapid internet technology, spending patterns of Indonesian people shifted. Shopping activities that previously could only be done in-person in stores, now can be done with internet technology known as online shopping. Online shopping can be accessed through digital applications known as e- commerce applications such as gofood and Facebook, in this case, there is a formulation of the problem in this research, namely to find out how the marketing communication strategy process is, as well as how it is implemented and the benefits e-commerce Bakso Terlena are complacent. The theoretical basis used in this study is marketing communications and the application of e-commerce. The approach method in this research is qualitative. The source of this research is the owner of Bakso Terlena who is complacent. The results of this study indicate that the marketing communication process through e-commerce implemented by the complacent Bakso Terlena owner provides benefits and advantages for the complacent Bakso Terlena owner such as saving time, expanding marketing reach and having flexible time in serving consumers.